Entrepreneurial Avenues Through Sweet Revolution (International Journal of Food and Nutritional Sciences, 2022)
India's economy has relied heavily on farming and related industries since its independence. While the contributions of the secondary and tertiary sectors have grown in recent years, agriculture continues to play a significant role in the economy. High demand exists for Indian honey on the global market since the country is consistently ranked among the top five producers of honey. Considering the demand and entrepreneurial opportunities, an initiative called Sweet Revolution (Mithi Kranthi) with the goal of reviving and improving honey output by means of beekeeping has been launched. This paper discusses the entrepreneurial avenues available to farmers and those involved in allied activities through the sweet revolution. Beekeeping is an agricultural pursuit that offers significant potential and prospects in India's many agro-climatic zones, making it a popular choice for economically disadvantaged rural residents such as landless labourers, farmers, rural youth, and women. This revolution has created new entrepreneurial avenues and jobs for all farmers and those who are allied with farming. The incentives indeed encourage rural youth to be attached to their roots.